1995
DOI: 10.1016/0040-1951(94)00173-7
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic regime of the southern Kurile Trench as revealed by multichannel seismic lines

Abstract: The analysis of the two multichannel seismic reflection records P-855 and P-856 reveals the complexity of the tectonic structure of the Kurile margin. The absence of trench fill and the relatively constant thickness of the subducted sediments on top of the oceanic basement shows that little or no accretion is occurring at present. The lower slope is characterized by active thrusting within a small accretionary prism. The toe of the middle slope is a more consolidated unit that constitutes an efficient buttress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…2 and 5). The upper terrace is underlain by wellstratifi ed refl ectors (Schnürle et al, 1995;TuZino et al, 2006) and possibly formed via a combination of subsidence and regional tilting (Klaeschen et al, 1994). TuZino et al (2006) reported the formation of half-grabens along the upper terrace Table DR2).…”
Section: Coastal and Submarine Areasmentioning
confidence: 95%
See 2 more Smart Citations
“…2 and 5). The upper terrace is underlain by wellstratifi ed refl ectors (Schnürle et al, 1995;TuZino et al, 2006) and possibly formed via a combination of subsidence and regional tilting (Klaeschen et al, 1994). TuZino et al (2006) reported the formation of half-grabens along the upper terrace Table DR2).…”
Section: Coastal and Submarine Areasmentioning
confidence: 95%
“…The slope between the upper and lower terraces exceeds 5° and is covered by a 600-mthick series of low-amplitude refl ections oriented parallel to the slope and underlain by weakly folded Neogene sediments (Schnürle et al, 1995). Uplift of this slope might have resulted from the underplating of sediment within the subduction zone (Klaeschen et al, 1994).…”
Section: Coastal and Submarine Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower slope is bounded by the outer high that consists of non-layered acoustic basements ( Fig. 5B and C) (Honza et al, 1978;Klaeschen et al, 1994;Schnürle et al, 1995). The sediments of the lower slope represent the formation of a half-graben, suggesting Fig.…”
Section: Seismic Profilesmentioning
confidence: 96%
“…Even where no major de´collements are recorded, the thickness may not be original. In the Kurile trench, the pelagic sediments have been thickened tectonically by a factor of 2 as they approached the trench, and inter-tongue with distal turbidites before being subducted or accreted (Schnu¨rle et al, 1995).…”
Section: Provenance Of the Golam Formationmentioning
confidence: 99%